Counselling Services as a Predictor of Bullying Prevention Among Vocational Students: A Quantitative Study in an Electrical Engineering Department - Ariesta Prameswari; Acep Nurlaeli; Wahidin (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
Bullying remains a persistent challenge in Indonesian vocational secondary schools, particularly in male-dominated technical departments where hierarchical peer dynamics may normalise aggressive conduct. School counselling services represent a preventive resource for fostering the socio-emotional competencies associated with prosocial student behaviour, yet quantitative evidence of this association in the specific context of electrical engineering vocational programmes remains limited. This study examines the predictive relationship between students’ perceptions of counselling service quality and their self-reported bullying prevention orientation. Using a quantitative causal-associative design, data were collected from 66 Grade XI students in the Electrical Power Installation Technology department at SMKN 1 Karawang through a structured Likert-scale questionnaire, employing total population sampling. Both variables were measured as student perceptions and operationalised through validated multi-indicator instruments whose items were tested for validity (r > 0.30) and reliability (Cronbach’s α > 0.70). Data were analysed using simple linear regression after confirming normality and linearity assumptions. Results indicate that students’ perception of counselling service quality is a strong positive predictor of their bullying prevention orientation (β = 0.908, R² = 0.753, p < 0.001), with counselling service perception accounting for approximately 75.3% of the variance in bullying prevention scores. These findings suggest that optimising students’ experience of counselling services particularly through problem-solving techniques that build conflict-management capacity is associated with substantially stronger bullying prevention attitudes and behaviours, as perceived by students themselves. Implications for school policy and counselling practice are discussed, with attention to the study’s methodological limitations.